Regional inventory approach to estimate methane emissions based on soil-land use classes - Glatzel, Stephan; Bareth, Georg (ERDKUNDE, 2006)
Regional estimations of methane (CH4) emissions employing process-based models are often not possible due to a lack of input parameters at the required spatial resolution. On the other hand, national greenhouse gas inventories are not able to express emissions with sufficient spatial resolution. We assembled a global CH4 flux database and assigned each flux estimate to a soil-land use combination. We applied the median CH4 fluxes from these soil-land use combinations to a remote sensing and GIS generated soil and land use map of the Allgäu region in southwestern Germany. Our CH4 emission estimate from the database for the region was 5.6 kg C ha-1 a-1. Comparison of CH4 fluxes from the database with measured local fluxes resulted in a two- to threefold over-estimation by the database estimate. We conclude that our approach delivers a plausible estimate of CH4 fluxes at the regional scale and should be further evaluated in other regions.